No influence of BCR-ABL1 transcript types e13a2 and e14a2 on long-term survival: results in 1494 patients with chronic myeloid leukemia treated with imatinib - Pfirrmann, Markus; Saußele, Susanne; Hehlmann, Rüdiger (Journal of cancer research and clinical oncology, 2017)
PurposeThe genomic break on the major breakpoint cluster region of chromosome 22 results in two BCR-ABL1 transcripts of different sizes, e14a2 and e13a2. Favorable survival probabilities of patients with chronic myeloid leukemia (CML) in combination with too small patient samples may yet have obstructed the observation of differences in overall survival of patients according to transcript type. To overcome potential power problems, overall survival (OS) probabilities and probabilities of CML-related death were analyzed in 1494 patients randomized to first-line imatinib treatment.MethodsOS probabilities and probabilities of dying of CML were compared using the log-rank or Gray test whichever was appropriate. Both tests were stratified for the EUTOS long-term survival score.ResultsBetween the groups with a single transcript, neither OS probabilities (stratified log-rank test: p = 0.106) nor probabilities of CML-related death were significantly different (stratified Gray test: p = 0.256). Regarding OS, the Cox hazard ratio (HR) of transcript type e13a2 (n = 565) to type e14a2 (n = 738) was 1.332 (95% CI 0.940-1.887). Considering probabilities of leukemia-related death, the corresponding subdistribution HR resulted in 1.284 (95% CI 0.758-2.176). Outcome did not change if patients with both transcripts (n = 191) were added to the 738 with type e14a2 only.ConclusionsThe prognostic association of transcript type and long-term survival outcome was weak and without clinical relevance. However, earlier reported differences in the rate and the depth of molecular response could be relevant for the chance of successfully discontinuing TKI treatment. The effect of transcript type on molecular relapse after discontinuation is unknown, yet.